Contemporary religiosities : emergent socialities and the post-nation state - Kapferer, Bruce; Telle, Kari; Eriksen, Annelin (Berghahn Books, 2010)
The last decade has seen an unexpected return of the religious, and with it the creation of new kinds of social forms alongside new fusions of political and religious realms that high modernity kept distinct. For a fuller understanding of what this means for society in the context of globalization, it is necessary to rethink the relationship between the religious and the secular; the contributors - all leading scholars in anthropology - do just that, some even arguing that secularization itself now takes a religious form. Combining theoretical reflection with vivid ethnographic explorations,